Exploiting Curcumin Synergy With Natural Products Using Quantitative Analysis of Dose–Effect Relationships in an Experimental In Vitro Model of Osteoarthritis - D’Ascola, Angela; Irrera, Natasha; Ettari, Roberta; Bitto, Alessandra; Pallio, Giovanni; Mannino, Federica; Atteritano, Marco; Campo, Giuseppe M.; Minutoli, Letteria; Arcoraci, Vincenzo; Squadrito, Violetta; Picciolo, Giacomo; et al. (Frontiers in Pharmacology, 2019)
Drug combination is widely used to treat chronic inflammatory diseases. A similar strategy might be worth of interest to design plant-derived natural products to treat inflammatory conditions. Curcumin is a natural phenolic compound which shares anti-inflammatory activity with both flavocoxid, a flavonoid mixture of baicalin and catechin, and beta-caryophyllene, a biciclic sesquiterpene. The aim of this study was to investigate the synergy potential of curcumin with both flavocoxid and beta-caryophyllene in human articular chondrocytes triggered with lipopolysaccharide (LPS), in an experimental in vitro model of osteoarthritis. Human articular chondrocytes were stimulated with LPS alone or in combination with different treatments. Total RNA was extracted four hours after treatment to study Interleukin 1beta (IL-1beta), NF-kB and STAT3 mRNA expression. LPS prompted the expression of IL-1beta. Curcumin, flavocoxid and beta-caryophyllene suppressed IL-1beta expression with different IC50. A drug combination study was designed choosing 5 doses to demonstrate a synergistic effect of compounds, according to Chou and Talalay method. A median-effect equation was applied and finally, the combination index (CI) was used to clarify the nature of the compounds interaction (synergistic versus additive versus antagonistic inhibitory effects); CI<1, CI=1 and CI>1 indicated synergistic, additive and antagonistic effects, respectively. A synergistic action for the reduction of the inflammatory phenotype in human chondrocytes was observed for the combination curcumin-flavocoxid with a percentage from 10% to 90%, and for the combination curcumin-beta-caryophyllene from 50% to 90%. IC50 doses of either flavocoxid, beta-caryophyllene and curcumin alone or in combination were safe and did not affect cell vitality. Moreover, the same IC50 doses reduced the transcription factors NF-kB and STAT3 mRNA expression and interestingly the effects of the combination were greater than the natural products alone, thus suggesting that the site where the synergy takes place could be at the signal transduction level. The results suggest that curcumin synergizes with either flavocoxid or beta-caryophyllene, exerting an anti-inflammatory activity and thus strongly suggesting the potential of a dual combination of these compounds for the management of osteoarthritis and unmasking a new feature of these natural products.